Application of Satellite Imagenary in Forestry for Georgia - Tatishvili, Marika R.; Mkurnalidze, Irine P.; Samkharadze, Inga G.; Chinchaladze, Lasha N. (Journals of Georgian Geophysical Society, 2018)
The one of Earth Observing System (EOS) program component is the investigation of influence of Earth vegetation on large-scale global processes. The most applicable product from satellite observation is Normalized Difference Vegetation Index that is used in observation on vegetation. The Normalized Difference Vegetation Index (NDVI) is an index of plant “greenness” or photosynthetic activity, and is one of the most commonly used vegetation indices. Vegetation indices are based on the observation that different surfaces reflect different types of light differently. Photosynthetically active vegetation, in particular, absorbs most of the red light that hits it while reflecting much of the near infrared light. Vegetation that is dead or stressed reflects more red light and less near infrared light. Vegetation indexies are important ecosystem variables widely used in variety of bio-geophysical applications. The Vegetation Health Product (VHP) consists of gridded weekly global vegetation indices (VCI, TCI and VHI) derived from AVHRR GAC orbital data for the global area. The Green Vegetation Fraction (GVF) system was developed to generate GVF as a NOAA-Unique Product (NUP) from data from the Visible Infrared Imager Radiometer Suite (VIIRS) sensor onboard Suomi National Polar-orbiting Partnership (SNPP) satellite, for applications in numerical weather and seasonal climate prediction models.  GVF will be produced as a daily rolling weekly composite at 4-km resolution (global scale) and 1-km resolution (regional scale). Satellite data are used to determine values of above listed indices for Georgian territory.